The Immune Change of the Lung and Bowel in an Ulcerative Colitis Rat Model and the Protective Effect of Sodium Houttuyfonate Combined With Matrine - Ni, Lulu; Jing, Shan; Zhu, Li; Yang, Xue; Wang, Xinyue; Tu, Su (Frontiers in Immunology, 2022)
OBJECTIVE: To explore the immune change of lung injury of Ulcerative colitis (UC) by observing the changes of inherent immunity and adaptive immunity of the lung and bowel in UC rat models after the treatment of Sodium Houttuyfonate combined with Matrine. METHOD: UC models were established with mucous membrane of colon allergize combine with TNBS-alcohol enteroclysis for 1 week and 5 weeks. 1-week experimental rats were divided into normal group and model group，5/each group. 5-weeks experimental rats were divided into normal group, model group, Sodium Houttuyfonate (2.9mg/ml) combined with Matrine Matrine (1.47mg/ml) and positive control sulfasalazine (10mg/ml), 5/each group. Intragastric administration for 5 weeks. The histopathological and fibrotic changes of lung and bowel were observed, the expression of Tumor Necrosis Factor (TNF)- α, interleukin (IL)-8 in the lung, bowel and serum were detected by radio-immunity and immunohistochemistry, and the mRNA expression of Toll-like receptor (TLR)-4, nuclear factor kappa (NF-κB), Macrophage migration inhibitory factor (MIF), Mucosal addressing cell adhesion molecule-1 (MadCAM1) and Pulmonary surfactant protein-A (SP-A) in the lung and bowel were detected by Real time-PCR. RESULT: Compared with normal group, the model rats had significant histopathological and fibrotic changes both in the lung and bowel, all treatment groups were improved. After treatment, TLR4, IL-8, MIF and TNF-α in the lung decreased (P＜0.05); NF-KB, IL-8 and MIF in the bowel increased (P＜0.05); MadCAM1 both in lung and bowel decreased (P＜0.05); SP-A decreased in bowel and increased in lung (P＜0.05). CONCLUSION: The cause of lung injury in this model was found to be related to inherent immunity and adaptive immunity, while the cause of bowel injury in this model was found to be mainly related to adaptive immunity. Sodium Houttuyfonate combined with Matrine could improve bowel and lung injury.